2015
DOI: 10.1021/acsami.5b04982
|View full text |Cite
|
Sign up to set email alerts
|

Foldable Transparent Substrates with Embedded Electrodes for Flexible Electronics

Abstract: We present highly flexible transparent electrodes composed of silver nanowire (AgNW) networks and silica aerogels embedded into UV-curable adhesive photopolymers (APPs). Because the aerogels have an extremely high surface-to-volume ratio, the enhanced van der Waals forces of the aerogel surfaces result in more AgNWs being uniformly coated onto a release substrate and embedded into the APP when mixed with an AgNW solution at a fixed concentration. The uniform distribution of the embedded composite electrodes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
(85 reference statements)
0
40
1
Order By: Relevance
“…In the absence of the aerogels, however, a nonuniform, sparse distribution of AgNWs was observed, as shown in the left FE-SEM image in Figure 2(b). Furthermore, the AFM surface image in the middle of Figure 2(b) shows traces of AgNWs that failed to be embedded, which corresponds to the valleys in the AFM line-scanning data in the right side of Figure 2 In our previous work, 13 we showed that aerogels could improve the transfer of AgNWs into a UV-curable polymer [Norland Optical Adhesive 68 (NOA 68)] because of the strong van der Waals interaction of the aerogels with the AgNWs and the matrix. The results in Figure 2(c) correspond well to those of our previous investigations.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…In the absence of the aerogels, however, a nonuniform, sparse distribution of AgNWs was observed, as shown in the left FE-SEM image in Figure 2(b). Furthermore, the AFM surface image in the middle of Figure 2(b) shows traces of AgNWs that failed to be embedded, which corresponds to the valleys in the AFM line-scanning data in the right side of Figure 2 In our previous work, 13 we showed that aerogels could improve the transfer of AgNWs into a UV-curable polymer [Norland Optical Adhesive 68 (NOA 68)] because of the strong van der Waals interaction of the aerogels with the AgNWs and the matrix. The results in Figure 2(c) correspond well to those of our previous investigations.…”
Section: Resultsmentioning
confidence: 68%
“…In our previous work, we showed that aerogels could improve the transfer of AgNWs into a UV‐curable polymer [Norland Optical Adhesive 68 (NOA 68)] because of the strong van der Waals interaction of the aerogels with the AgNWs and the matrix. The results in Figure (c) correspond well to those of our previous investigations . Contrary to the results in Figure (b,c) shows uniformly embedded, dense AgNWs on the surface of the PDMS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various polymer materials, such as PVA, PDMS, PMMA, polyimide, polyelectrolyte, poly(acrylate), etc., have been investigated for the fabrication of flexible transparent electrodes to meet specific requirements in practical applications. [164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181] Pei and coworkers have made a lot of contributions in this area and various polymer materials have been developed for the application of optoelectronic devices. [182][183][184][185][186][187][188][189][190][191][192][193]…”
Section: Formation Of Metal Nanowire Based Conductive Networkmentioning
confidence: 99%